1992
DOI: 10.2500/108854192778816933
|View full text |Cite
|
Sign up to set email alerts
|

Partial Albinism, Immunodeficiency, and Progressive White Matter Disease: A New Primary Immunodefiency

Abstract: We studied 12 children who presented with a recently recognized syndrome. The salient features of this new syndrome were recurrent fever; hepatosplenomegaly; pancytopenia: blond, golden to silvery gray hair; hypopigmented skin, progressive white maller demyelination; and early death. Seven patients died, four with severe central nervous system (CNS) involvement, and three with bone marrow failure and sepsis. Cutaneous anergy to recall antigens was present in all patients. Other immunological abnormalities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 5 publications
2
21
0
Order By: Relevance
“…The Rab‐GTPase, Rab27a, is associated with a genetic disorder leading to disease in humans. Genetic defects in the Rab27a gene cause a rare defect in patients known as Griscelli syndrome type 2 (GS2), which is characterized by pigmentary disorder associated with melanosome transport and severe immunodeficiency associated with defects in T cell, neutrophil, and natural killer cell function …”
Section: Vesicular Trafficking Mechanisms Regulating Neutrophil Functmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rab‐GTPase, Rab27a, is associated with a genetic disorder leading to disease in humans. Genetic defects in the Rab27a gene cause a rare defect in patients known as Griscelli syndrome type 2 (GS2), which is characterized by pigmentary disorder associated with melanosome transport and severe immunodeficiency associated with defects in T cell, neutrophil, and natural killer cell function …”
Section: Vesicular Trafficking Mechanisms Regulating Neutrophil Functmentioning
confidence: 99%
“…Genetic defects in the Rab27a gene cause a rare defect in patients known as Griscelli syndrome type 2 (GS2), which is characterized by pigmentary disorder associated with melanosome transport and severe immunodeficiency associated with defects in T cell, neutrophil, and natural killer cell function. [34][35][36][37][38] All of the functions of neutrophils rely on the correct trafficking of their different vesicular compartments and the delivery of their cargo to acceptor membranes or compartments. In this review, we will discuss how various Rab family members along with their effectors regulate trafficking of different granules subsets and consequently modulate neutrophil functions.…”
Section: Vesicular Trafficking Mechanisms Regulating Neutrophil Funmentioning
confidence: 99%
“…GS2 is a primary immunodeficiency with partial albinism [5,6]. Patients with GS2 develop a disorder characterized by malfunctioning of CTLs, impaired NK cell function [5,6] and defective neutrophil functions [6,7]. At the cellular level, defects in hematopoietic cells are caused by the inability of CTLs, NK cells, and neutrophils to secrete intragranular proteins into infected cells or the extracellular milieu as a result of deficient priming and fusion of secretory organelles.…”
Section: Rab27a and Effectors In Human Immunodeficienciesmentioning
confidence: 99%
“…Two early case reports suggested that patients with GS have defects in the function of their granulocytes [6,7]. One of those studies showed abnormal bactericidal activity in some of the patients evaluated [6], whereas the other work reported abnormalities in the phagocytic activity of neutrophils only in a subpopulation of the patients under study [7]. Although those studies supported the idea that the function of neutrophils is impaired in Rab27a deficiency, further studies were necessary to increase our knowledge of the role played by this GTPase and its effector molecules in neutrophil function.…”
Section: Rab27a and Effectors In Human Immunodeficienciesmentioning
confidence: 99%
See 1 more Smart Citation